Effect of a stepped-care intervention delivered by lay health workers on major depressive disorder among primary care patients in Nigeria (STEPCARE): a cluster randomised controlled trial (2019)
Background Little is known about how to scale up care for depression in settings where non-physician lay workers constitute the bulk of frontline providers. We aimed to compare a stepped-care intervention package for depression with usual care enhanced by use of the WHO Mental Health Gap Action Programme intervention guide (mhGAP-IG). Methods We did a cluster-randomised trial in primary care clinics in Ibadan, Nigeria. Eligible clinics were those with adequate staffing to provide various 24-h clinical services and with regular physician supervision. Clinics (clusters), anonymised and stratified by local government area, were randomly allocated (1:1) with a computer-generated random number sequence to one of two groups: an intervention group in which patients received a stepped-care intervention (eight sessions of individual problem-solving therapy, with an extra two to four sessions if needed) plus enhanced usual care, and a control group in which patients received enhanced usual care only. Patients from enrolled clinics could participate if they were aged 18 years or older, not pregnant, and had moderate to severe depression (scoring ≥11 on the nine-item patient health questionnaire [PHQ-9]). The primary outcome was the proportion of patients with remission of depression at 12 months (a score of ≤6 on the PHQ-9, with assessors masked to group allocation) in the intention-to-treat population. This trial is registered with the International Standard Randomised Controlled Trials Number registry (ISRCTN46754188) and is completed. Findings 35 of 97 clinics approached were eligible and agreed to participate, of which 18 were allocated to the intervention group and 17 to the control group. 1178 patients (631 [54%] in the intervention group and 547 [46%] in the control group) were recruited between Dec 2, 2013, and June 29, 2015, among whom 976 (83%) were female and baseline mean PHQ-9 score was 13·7 (SD 2·6). Of the 562 (89%) patients in the intervention group and 473 (86%) in the control group who completed 12-month follow-up, similar proportions in each group had remission of depression (425 [76%] in the intervention group vs 366 [77%] in the control group; adjusted odds ratio 1∙0 [95% CI 0·70–1·40]). At 12 months, 17 (3%) deaths, one (<1%) psychotic illness, and one (<1%) case of bipolar disorder in the intervention group, and 16 deaths (3%) and one (<1%) case of bipolar disorder in the control group were recorded. No adverse events were judged to be related to the study procedures. Interpretation For patients with moderate to severe depression receiving care from non-physician primary health-care workers in Nigeria, a stepped-care, problem-solving intervention combined with enhanced usual care is similarly effective to enhanced usual care alone. Enhancing usual care with mhGAP-IG might provide simple and affordable approach to scaling up depression care in sub-Saharan Africa.